Strategies For Optimizing Traditional Market Retribution: A Study In Purworejo Regency - Arief Rahman; Ahada Nur Fauziya; Tiyas Kurnia Sari3 (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Regency, was conducted using an integrated mixed method which combines quantitative and qualitative approaches to process various data collected to formulate policies and strategies in addressing a public issue (Burch & Heinrich, 2015). This study used secondary data from Statistics Indonesia, regulations, research results, and primary data from interviews, observations, and focus group discussions involving relevant stakeholders. Data analysis involved classification analysis, macro data analysis, and SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. Based on the SWOT analysis, several programs can be carried out by the Purworejo District Government to maximize the potential of its regional markets. Promote traditional markets after revitalization to increase public awareness of the positive changes in the market. Using social media, advertisements, and promotional campaigns to reach more potential visitors. Some of the related activities include; Socialization through social media, Official website development, Promotional video campaign, Photography competition, Loyalty program.